Doliolid (Tunicata, Thaliacea) Blooms in the Southeastern Gulf of Alaska as a Result of the Recent Marine Heat Wave of 2014–2016 - Pinchuk, Alexei I.; Batten, Sonia D.; Strasburger, Wesley W. (Frontiers in Marine Science, 2021)
The eastern North Pacific experienced a prolonged heat wave in 2014–2016 manifested by high sea surface temperature anomalies in the south-central Gulf of Alaska (GOA). The event provided a natural experiment on the response of the southern GOA ecosystem to a dramatic change in sea temperature. Spatial and temporal variability in zooplankton communities following the culmination of the heat wave was investigated as a part of the NOAA Eastern GOA Ecosystem Assessment program in 2016–2017. Here, for the first time in the GOA, we report consistent observations of doliolid (Dolioletta tritonis) swarms observed in the upper mixed layer beyond the shelf break during both years, with the maximal density of 3,847 ind m–3 recorded in August 2016 and coinciding with the location of an offshore cyclonic mesoscale eddy. Doliolid density was significantly lower on the shelf. The long-term Continuous Plankton Recorder (CPR) data indicated that doliolid blooms in the south-central GOA may have occurred in the past two decades during El-Nino events. Coincidentally, doliolids prevailed in the diets of juvenile sablefish collected along the eastern coast of GOA both during the 2014–2016 heat wave and during 1997–1998 El Nino. Thus, we speculate that warming trends may increase the importance of doliolids in the GOA pelagic food web.